Atheroregressive Potential of the Treatment with a Chimeric Monoclonal Antibody against Sulfated Glycosaminoglycans on Pre-existing Lesions in Apolipoprotein E-Deficient Mice - Brito, Victor; Mellal, Katia; Zoccal, Karina F.; Soto, Yosdel; Ménard, Liliane; Sarduy, Roger; Faccioli, Lucia H.; Ong, Huy; Vázquez, Ana M.; Marleau, Sylvie (Frontiers in Pharmacology, 2017)
The retention of lipoprotein particles in the intima, in particular to glycosaminoglycan side chains of proteoglycans, is a critical step in atherosclerosis initiation. Administration of chP3R99, a chimeric mouse/human monoclonal antibody inducing an anti-idiotypic network response against glycosaminoglycans was previously shown to prevent atherosclerotic lesion progression, yet its effect in the late-stage progression of lesions remains unknown. This study investigated the effect of chP3R99 at a late stage of disease development in apolipoprotein E-deficient mice and the vascular mechanisms involved. Male apolipoprotein E-deficient mice were fed a high fat high cholesterol diet from 4 to 19 weeks old, at which time mice were fed normal chow and 5 doses of chP3R99 (50 µg) or isotype-matched IgG (hR3) were administered subcutaneously weekly for the first 3 administrations, then at weeks 24 and 26 before sacrifice (week 28). Lesions progression was reduced by 88% in treated mice with no change in total plasma cholesterol levels, yet with increased sera reactivity to chP3R99 idiotype and heparin, suggesting the induction of an anti-idiotype antibody cascade against glycosaminoglycans, which was likely related with the atheroprotective effect. chP3R99 treatment initiated regression in a significant number of mice. Circulating levels of interleukin-6 were reduced along with a striking diminution of inflammatory cell accumulation in the vessel wall, and of VCAM-1 labeling in vivo. The ratio of IL-10/iNOS gene expression in aortas increased in chP3R99-treated mice. In conclusion, our results show that treatment with chP3R99 reduces vascular inflammatory burden and halts lesion progression with potential for regression in the late phase of the disease in atherosclerotic mice, and support the therapeutic intervention against glycosaminoglycans as a novel strategy to reverse atherosclerosis.